Consideration of Network Constraints in the Turkish Day Ahead Electricity Market. (November 2018) - Sahin, Cem
Highlights: A new model for the Turkish Electricity Market including network equations is introduced. The development of Turkish Electricity Markets is summarized. The model is demonstrated in three different networks with increasing sizes. It is shown that the solution of the proposed model obtains optimal system cost. The solution performance of the proposed solution methodology is shown. Abstract: This paper proposes a new model for the Turkish Day Ahead Electricity Market including network equations. The existing one does not implicitly consider the power flow limitations, and these are considered separately that might result with a suboptimal day-ahead schedule. The dc network equations are added to the model, which is used to determine the Day Ahead System Sell and Buy Decisions and System Marginal Price in day-ahead planning. The impact of integration of network equations is exhibited using a small 6-bus network, mid-sized Turkish northwest sub-system, and full Turkish electric power system.